Te amé entre la maleza (2017)
"This research is conceived as a discursive project about the lies that build us as human beings and how they materialize through the creation of fictions, resulting in a poetic proposal. I loved you in the undergrowth is a wardrobe collection that brings together a sum of lost loves, half truths and abysmal lies. It is the result of a discourse full of fallacies that tell you in childhood and never agree with that incoherence that we call life. The clothes carry with them lies, familiar faces and emotions of contraband." -- Tomado del Formato de Documento de Grado.